Explaining A Narrative in The Critical Philosophy of History - Arif Akhyat (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2019)
This paper explains the narrative in the study of history which has only been understood as a way of telling what should have happened, not what really happened. Narrative as a philosophical thought will be able to reveal not only the factual side but also the actual side. As a philosophical thought, the narrative should be able to provide a new understanding that narration is not just telling (history as a story), but also how can narration be used to explain the historical actuality? Through a new understanding of narrative, history actually as science becomes parallel to other sciences as philosophy. Historical narratives then present